Desmoid tumor initially unresectable – About two cases - Sara Senti Farraraons (Shiraz University of Medical Sciences, 2019)
Desmoid tumor, also called aggressive fibromatosis, is a rare fibroblastic proliferation of connective tissue and skeletal muscle aponeurosis. The aetiology of desmoid tumours is poorly understood, but they have been related with oestrogen stimuli, previous trauma, surgical interventions and pregnancy. Although it is characterized by not having potential for metastasize or differentiate, it is a non-encapsulated lesion, with an infiltrative growth and unpredictable behaviour. In this way, it could have either an aggressive pattern, when compared with other low degree malignancy sarcomas, or a very indolent one, even with spontaneous regression. Therapeutic options in desmoid tumours have been changing over these last years, as surgery upfront in asymptomatic patients has been superseded by active surveillance. However, treatment has to be individualized in some specific scenarios such as intra-abdominal lesions. We present two cases of patients diagnosed with an intra-abdominal desmoid tumour with threatening behaviour, the treatment approach and final resolution.